2014
DOI: 10.1155/2014/818797
|View full text |Cite
|
Sign up to set email alerts
|

Morphoanatomical and Biochemical Changes in the Roots of Rice Plants Induced by Plant Growth-Promoting Microorganisms

Abstract: The goal of the present study was to characterize anatomical and biochemical changes in rice plant roots in response to seed treatment with rhizobacteria (Burkholderia pyrrocinia (R-46) + Pseudomonas fluorescens (R-55)) and Trichoderma asperellum (Ta: mixture of strains T-06, T-09, T-12, and T-52). The experimental design was completely randomized, with six treatments (R-46, R-55, R-46 + R-55, Ta+ R-46 + R-55, Ta, and control) and ten replicates. Treatments Ta and R-46 + R-55 increased the root length and diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 36 publications
(37 reference statements)
2
26
0
6
Order By: Relevance
“…and Burkolderia sp. have attested their growth-promoting potential in rice Rêgo, Borges, Filippi, Gonc ßalves, & Silva, 2014) and Brachiaria brizantha (Lopes et al, unpublished). These rhizobacteria are known to increase the auxin synthesis, nutrient uptake (e.g., nitrogen, phosphorus and iron), chlorophyll content, photosynthetic rate and biomass production (Ahemad & Kibret, 2014;Nascente et al, 2016).…”
mentioning
confidence: 99%
“…and Burkolderia sp. have attested their growth-promoting potential in rice Rêgo, Borges, Filippi, Gonc ßalves, & Silva, 2014) and Brachiaria brizantha (Lopes et al, unpublished). These rhizobacteria are known to increase the auxin synthesis, nutrient uptake (e.g., nitrogen, phosphorus and iron), chlorophyll content, photosynthetic rate and biomass production (Ahemad & Kibret, 2014;Nascente et al, 2016).…”
mentioning
confidence: 99%
“…Control WR seeds had a 2% reduction in germination Mean values (mg g -1 Ms) obtained in a previous study by Rêgo et al (2014).…”
Section: Seed Germination Seedling Vigor and Growth Promotion In Plmentioning
confidence: 75%
“…Growth promotion can take place directly (inducing changes physiological, biochemical, molecular and morphological, anatomical) or indirect (through induction of resistance to biotic and abiotic stresses) defined by Bach et al (2016). Studies carried out by Filippi et al (2011), Rêgo et al (2014), Nascente et al (2016), and Bueno et al (2017), indicate that isolates BRM-32111 and BRM-32113, present action to promote growth in plants of both forms (direct and indirect).…”
Section: Seed Germination Seedling Vigor and Growth Promotion In Plmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that rice plants, when faced with a biotic stimulus, such as inoculation of fungi isolate, had higher deposition of lignin in their roots, which varied according to the fungi isolate (Rêgo et al 2014). Thus, cassava genotypes with this characteristic may be more adapted to poorly drained soils, preventing root rot.…”
Section: Discussionmentioning
confidence: 99%